Robotic Arm-Assisted versus Manual Total Knee Arthroplasty: A Propensity Score-Matched Analysis - Samuel, Linsen T.; Karnuta, Jaret M.; Banerjee, Aditya; Briskin, Isaac; Cantrell, William A.; George, Joseph W.; Higuera-Rueda, Carlos A.; Kamath, Atul F.; Khlopas, Anton; Klika, Alison; Krebs, Viktor E.; Mesko, Nathan W.; Mont, Michael A.; Murray, Trevor G.; Piuzzi, Nicolas S.; Shah, Paras; Stearns, Kim; Sultan, Assem A.; Molloy, Robert M. (The Journal of Knee Surgery, 2021)
The purpose of this study was to compare (1) operative time, (2) in-hospital pain scores, (3) opioid medication use, (4) length of stay (LOS), (5) discharge disposition at 90-day postoperative, (6) range of motion (ROM), (7) number of physical therapy (PT) visits, (8) emergency department (ED) visits, (9) readmissions, (10) reoperations, (11) complications, and (12) 1-year patient-reported outcome measures (PROMs) in propensity matched patient cohorts who underwent robotic arm-assisted (RA) versus manual total knee arthroplasty (TKA). Using a prospectively collected institutional database, patients who underwent RA- and manual TKA were the nearest neighbor propensity score matched 3:1 (255 manual TKA:85 RA-TKA), accounting for various preoperative characteristics. Data were compared using analysis of variance (ANOVA), Kruskal–Wallis, Pearson's Chi-squared, and Fisher's exact tests, when appropriate. Postoperative pain scores, opioid use, ED visits, readmissions, and 1-year PROMs were similar between the cohorts. Manual TKA patients achieved higher maximum flexion ROM (120.3 ± 9.9 versus 117.8 ± 10.2, p = 0.043) with no statistical differences in other ROM parameters. Manual TKA had shorter operative time (105 vs.113 minutes, p < 0.001), and fewer PT visits (median [interquartile range] = 10.0 [8.0–13.0] vs. 11.5 [9.5–15.5] visits, p = 0.014). RA-TKA had shorter LOS (0.48 ± 0.59 vs.1.2 ± 0.59 days, p < 0.001) and higher proportion of home discharges (p < 0.001). RA-TKA and manual TKA had similar postoperative complications and 1-year PROMs. Although RA-TKA patients had longer operative times, they had shorter LOS and higher propensity for home discharge. In an era of value-based care models and the steady shift to outpatient TKA, these trends need to be explored further. Long-term and randomized controlled studies may help determine potential added value of RA-TKA versus manual TKA. This study reflects level of evidence III.
Keywords: robotic arm-assisted; total knee arthroplasty; manual; postoperative outcomes; propensity score matched; patient-reported outcome measure